1999
DOI: 10.1002/1531-8249(199905)45:5<568::aid-ana4>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

Neuroimaging evidence of progressive neuronal loss and dysfunction in temporal lobe epilepsy

Abstract: Whether temporal lobe epilepsy is the result of an isolated, early injury or whether there is ongoing neuronal dysfunction or loss due to seizures is often debated. We attempt to address this issue by using magnetic resonance techniques. Proton magnetic resonance spectroscopic imaging can detect and quantify focal neuronal dysfunction or loss based on reduced signals from the neuronal marker N‐acetylaspartate (NAA), and magnetic resonance imaging (MRI)‐based measurements of hippocampal volumes (MRIvol) can qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
148
2
6

Year Published

1999
1999
2012
2012

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 251 publications
(168 citation statements)
references
References 52 publications
12
148
2
6
Order By: Relevance
“…In partial epilepsy, one study reported that seizure frequency correlates with the degree of NAA decrease (24). In a recent article investigating 82 patients with TLE, Tasch et al (25) found that NAA/Cr was negatively correlated with the duration of epilepsy and the number of generalized tonic-clonic seizures. The only experimental study, which addressed a question similar to ours by comparing increased electrical brain activity and metabolic changes with phosphorus ("P)-spectroscopy in the penicillin epilepsy model in rats, was reported by Karlik et al (26).…”
Section: Discussionsupporting
confidence: 87%
“…In partial epilepsy, one study reported that seizure frequency correlates with the degree of NAA decrease (24). In a recent article investigating 82 patients with TLE, Tasch et al (25) found that NAA/Cr was negatively correlated with the duration of epilepsy and the number of generalized tonic-clonic seizures. The only experimental study, which addressed a question similar to ours by comparing increased electrical brain activity and metabolic changes with phosphorus ("P)-spectroscopy in the penicillin epilepsy model in rats, was reported by Karlik et al (26).…”
Section: Discussionsupporting
confidence: 87%
“…Moreover, proton magnetic resonance spectroscopy revealed that a bilateral reduction in the concentration of N-acetyl-aspartate can exist in many patients with focal epilepsies. This is probably a sign of neuronal loss or dysfunction that extends ipsiand contralateral to the epileptogenic region (45,46). One practical implication of the largely bilateral changes detected is that paired TMS might be of no value in localizing the epileptogenic area.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] Volumetric abnormalities have been reported in neuronal regions involved in the generation and propagation of seizures, including the hippocampus, [8][9][10][11] amygdala, 12 entorhinal cortex, 13 thalamus, 14 and also extratemporal regions 15,16 in patients with chronic temporal lobe epilepsy. Children with idiopathic generalized epilepsies have also shown distributed patterns of abnormality affecting the thalamus and frontal lobe.…”
mentioning
confidence: 74%
“…[17][18][19][20][21] It is not known whether the structural alterations developed during a vulnerable phase of cerebral development or are the cumulative effects of recurrent seizures 22 or are a combination of these factors acting synergistically. 11 To determine whether antecedent neurobiologic alterations are present, assessment could be performed in a population of patients with newonset seizures, which would exclude the confounding effects of recurrent seizures and long-term antiepileptic medications on the brain.…”
mentioning
confidence: 99%